Strategi Pengembangan Kurikulum di Madrasah Ibtidaiyah Swasta Nurus Salam Deli Tua - Sopan Sofian; Candra Wijaya; Muhammad Rifa’i (Universitas Negeri Malang, 2020)
Abstract: This Nurus Salam Private Elementary School is one of the educational institutions of the Nurus Salam educational foundation. However, in its implementation, this Nurus Salam Private Elementary School seems more advanced than other educational institutions so I am interested in studying more deeply how the curriculum development is applied in this Nurus Salam Private Elementary School. Because the progress of Elementary Schools or other educational institutions is marked by several factors, including the factor of a good and neatly arranged curriculum. In writing this thesis, the researcher used a qualitative research method. Data collection techniques in this study were in the form of interviews, observations and documentation studies. There are several steps taken by MIS Nurus Salam in determining the objectives of the Curriculum. The first is collecting data from the Community, the second is analyzing student needs, the third is ensuring that the curriculum used is in accordance with national and international standards. The first step taken by MIS Nurus Salam in determining the content of the curriculum is to analyze the needs of students and the surrounding community, then review the existing curriculum, MIS Nurus Salam also asks for suggestions from parents and teachers, In addition, MIS Nurus Salam also invites practitioners to provide input on the content of their curriculum. Furthermore, integrating the latest education policies into the content of the curriculum to ensure that the education provided is in accordance with the standards and needs of the times.Keywords: Strategy, Curriculum Development, Madrasah. Abstrak: Madrasah Ibtidaiyah Swasta Nurus Salam ini merupakan salah satu lembaga pendidikan dari yayasan perguruan Nurus salam. Namun, dalam pelaksanaannya Madrasah Ibtidaiyah Swasta Nurus Salam ini tampak lebih maju dari lembaga pendidikan lainnya sehingga saya tertarik untuk mengkaji lebih dalam bagaimana pengembangan kurikulum yang diterapkan di Madrasah Ibtidaiyah Swasta Nurus Salam ini. Karena kemajuan Madrasah Ibtidaiyah atau lembaga pendidikan lainnya ditandai dengan beberapa faktor, diantaranya dari faktor kurikulumnya yang bagus dan tertata rapi. Dalam penulisan ini peneliti menggunakan metode penelitian kualitatif, Teknik pengumpulan data dalam penelitian ini berupa wawancara, observasi dan studi dokumentasi. Ada beberapa Langkah yang dilakukan oleh MIS Nurus Salam dalam menentukan tujuan Kurikulum. Yang pertama mengumpulkan data dari Masyarakat, kedua menganalisis kebutuhan siswa, ketiga memastikan bahwa kirikulum yang yang digunakan sesui dengan standar nasional maupun internasional. Langkah pertama yang dilakukan MIS Nurus Salam dalam menentukan isi kurikulum ialah menganalisis kebutuhan siswa dan Masyarakat sekitar selanjunya mengkaji kurikulum yang sudah ada, MIS Nurus Salam juga meminta saran dari orang tua dan guru, Salain itu MIS Nurus Salam juga mengundang praktisi untuk memberikan masukan tentang isi kurikulum mereka. Selanjunya Mengintegrasikan kebijakan pendidikan terbaru ke dalam isi kurikulum guna memastikan bahwa pendidikan yang diberikan sesuai dengan standar dan kebutuhan zaman.Kata kunci: Strategi, Pengembangan Kurikulum, Madrasah.